How Green Marketing and Product Quality Influence Buying Interest Using Green Brand Image - Gemuruh Chairul Umam; Arry Widodo (Pusat Penerbitan dan Publikasi Ilmiah, Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2022)
IKEA is a company that implements a marketing strategy through the concept of green marketing. Now, IKEA Indonesia continues to expand by opening its newest branch, namely in West Java which is located in Kota Baru Parahyangan, this indicates that the public's interest and enthusiasm for what IKEA wants to offer with a green marketing strategy approach. This study aims to determine the effect of green marketing, product quality on buying interest through green brand image as an intervening variable. The method used quantitative with descriptive and causal research as well as SEM-PLS analysis method. The sampling technique used non-probability sampling technique with a total sample of 384 consumers IKEA Kota Baru Parahyangan. The results of descriptive analysis on green marketing, product quality, green brand image and buying interest are in good category and the results can be concluded that Green marketing has a positive effect on buying interest through green brand image as an intervening variable at IKEA Kota Baru Parahyangan. Product quality has a positive effect on buying interest through green brand image as an intervening variable at IKEA Kota Baru Parahyangan